Pengaruh Pelatihan, Kompensasi dan Motivasi Kerja Terhadap Prestasi Kerja Karyawan Bagian Industri Pemasaran Di Perum Perhutani Unit I Jawa Tengah - Okky Setiawan; Sri Suryoko; Reni Shinta Dewi (Jurnal Ilmu Administrasi Bisnis, 2012)
Perum Perhutani is a company works in the sector of forest manufacturing covering the wood base and non wood base resource. The knowldge, skill and, detail abilities are important for the high productivity. The work of employee allows the good working environment, high motivation, comapny that runs well, so that the companys’ goal can be achieved. The trainings, compensation and work motivation should be taken into consideration in order to improve the achievement of the employee. The aim of this reserach is to prove the influence trainings, compensation, and work motivation both as stimolous and partial. The method of reserach used for this reserach is the explanatory research. The method was questionary method, interview, and library reserach. The total number of the respondent is 55 people taken with the propotional sampling method. The technique of analysis is the analysis of double linear regretion supperted by SPSS17 program for Windows. The result of this research is that the training, compensation, and motivation towards Perum Perhutani Unit 1 Central Java shows statisfactory result. The traiings, compensation, and motivation brings significant result towards the work achievements. The variable of trainings and motivayion gives very strong influence towards the work achivements by 66.3% and 33.7% was influenced by the other veriable. The result of this research is that the training, compensation, and motivation towards Perum Perhutani Unit 1 Central Java shows statisfactory result. The traiings, compensation, and motivation brings significant result towards the work achievements. The variable of trainings and motivayion gives very strong influence towards the work achivements by 66.3% and 33.7% was influenced by the other veriable. Suggestions can be submitted is improving the quality of equipment and comfort room, claim medical expenses of patients to be more easy. .And for further research are discussed variables other than training, compensation and motivation, among others, the work environment and work discipline